Drivers of conservation crimes in the Rungwa-Kizigo-Muhesi Game Reserves, Central Tanzania - Kwaslema Malle Hariohay; Peter S. Ranke; Robert D. Fyumagwa; Jafari R. Kideghesho; Eivin Røskaft (Global Ecology and Conservation, 2019)
Conservation crimes are posing serious threats to wildlife species and biodiversity of the Rungwa-Kizigo-Muhesi-Game-Reserves. Devising effective strategies to reduce risks to as low as reasonably possible of these crimes, calls for adequate information on factors driving people to commit these crimes. Data for this study were obtained from 315 respondents in 20 villages and 316 people who were arrested for committing different conservation crimes in the Rungwa-Kizigo-Muhesi-Game-Reserves. Our results suggest that arrested respondents were typically young adult males with limited alternative sources of income and owning virtually no livestock or land. There were heterogeneous drivers for each type of conservation crime. To address the challenge of conservation crimes in the Reserve, we recommend, among other strategies, the establishment of effective conservation education programmes, strengthening law enforcements as a deterrence method, and development of entrepreneurship skills to enhance employment. Keywords: Bushmeat poaching, Conservation criminology, Elephant, Illegal timber logging, Wildlife poaching